(untitled) (Journal of Engineering, 2012)
In most manufacturing processes, and in spite of statistical control, several process capability indices refer to non conformance of the true mean (µc ) from the target mean ( µT ), and the variation is also high. In this paper, data have been analyzed and studied for a blow molded plastic product (Zahi Bottle) (ZB). WinQSB software was used to facilitate the statistical process control, and process capability analysis and some of capability indices. The relationship between different process capability indices and the true mean of the process were represented, and then with the standard deviation (σ ), of achievement of process capability value that can reduce the standard deviation value and improve production out of theoretical control limitations and cost reduction. The study exhibits that when adjusting the center to the target value by adjusting the mold to the machine, the capability index (C ) enhanced by (14.56 %), capability index ( p C ) is enhanced by (14.48 %), pk capability index (Cpm ) is enhanced by (12.5 %) and accuracy index (Ca ) is enhanced by (14.49 %). The percentage of the specification band used up by the process ( P ) is reduced by (12.8 %) and the degree of variation increases.